Response to Kerr, Hedley, Pickstock, Ward and Soskice. - Williams, Rowan (Modern Theology, 2015)
The article discusses essays about theology created by several authors including Fergus Kerr, Catherine Pickstock, and Graham Ward. Topics discussed include the impact of the works of philosopher Ludwig Wittgenstein on the discourse about God, human speech and Platonism, and the connection between metaphysics and Christology.